ISLAMIC EDUCATIONAL DYNAMIC IN MINANGKABAU (AN 86-YEAR JOURNEY OF MADRASAH DINIYAH PASIA) - Fithri, Widia (Ar Raniry : International Journal of Islamic Studies, 2015)
Islamic Education in Minangkabau is one of the contributors to the Indonesian Muslim intellectuals. In the recent decade, such statement is resounded to reproduce Muslim intellectuals in the present and in the future. What and how is the history of Islamic education atmosphere in Minangkabau in maintaining its existence? This paper will explore one of the Islamic educational institutions in Minangkabau, Madrasah Diniyyah Pasia. In the world of Islamic education in Minangkabau, the name of Madrasah Diniyyah Pasia is that popular, but this Madrasah has survived though it has undergone several changes in its education system. Since July 1, 1992, the Madrasah has adopted a boarding school system. Some names recorded to have been in contact with the Madrasah are Sheikh Abdul Latif Syakur, Prof. Mahmud Yunus, Prof Zakiyah Derajat and Prof Hashim Djalal.